Emergency Room at Udayana University Hospital - Emyastuti, Ni Luh Wayan; Suarjana, I Ketut; Lesmana, Cokorda Bagus Jaya (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2024)
Background and objectives: The Emergency Department (ER) at Udayana University Hospital is required to provide quality health services in accordance with the Minimum Service Standards (SPM) set by the government. However, there are several SPM indicators that have not been achieved. Therefore, this research aims to develop a strategy to increase SPM achievement in the emergency room at Udayana University Hospital using the two-stage Delphi method. Method: A qualitative approach with a two-stage Delphi method was used to achieve this objective. Data was collected through in-depth interviews with 16 informants, FGDs and questionnaires. Results: The research found that internal factors categorized as strengths and weaknesses influenced the achievement of SPM in the IGD. External factors are classified into opportunities and threats. SWOT analysis shows that the IE matrix describes a grown and built organization. In the 4-Quadrant SWOT Matrix, it is in quadrant I which describes the opportunities and strengths of the organization and strategies that can be carried out with aggressive strategies. The TOWS matrix produces 11 alternative strategies which are ranked using the QSPM method. Alternative strategies generated using the Delphi method resulted in 6 priority strategies. Conclusion: From this research, 7 strength factors, 7 weakness factors, 4 opportunity factors and 3 threat factors were found at UNUD Hospital and there are 6 priority strategies that can be used to improve SPM IGD achievements.